IκBα Promoter Polymorphisms in Patients with Behçet's Disease. Issue 1 (2nd June 2013) - Hung, Yu-Hung; Wu, Cheng-Chin; Ou, Tsan-Teng; Lin, Chia-Hui; Li, Ruei-Nian; Lin, Yu-Chih; Tsai, Wen-Chan; Liu, Hong-Wen; Yen, Jeng-Hsien
Abstract : To investigate the role of IκBα promoter polymorphisms in the development of Behçet's disease, eighty-six patients with Behçet's disease and 120 healthy controls were enrolled in this study. The IκBα ; -881A/G, -826C/T, -550A/T, -519C/T, and -297C/T polymorphisms were measured by the method of polymerase chain reaction/ restriction fragment length polymorphism. This study demonstrated that the genotype frequencies of IκBα -826C/T and -826T/T were significantly higher in the patients with Behçet's disease than in the controls. Both in the dominant and in the recessive models, the patients with Behçet's disease have higher frequencies of the IκBα -826T containing genotype than the controls. The allele frequency of IκBα -826T was significantly increased in the patients with Behçet's disease. The frequencies of the IκBα -881A -826T -550A -519C -297C and IκBα -881A -826T -550A -519T -297C haplotypes were significantly higher in the patients with Behçet–s disease than in the controls. In contrast, the haplotype frequency of IκBα -881A -826C -550A -519C -297C in the patients with Behçet's disease was significantly decreased. This study also revealed that the Behçet's disease patients with IκBα -826T/T have higher prevalence of skin lesions than those without IκBα -826T/T. In summary, the IκBα -826T allele, IκBα -881A -826T -550A -519C -297C and IκBα -881A -826T -550A -519T -297C haplotypes might be associated with susceptibility to Behçet's disease. The IκBα -826T/T genotype was related to the development of skin lesions in the patients with Behçet's disease.